Trichotillomania (hair pulling disorder): Clinical characteristics, psychosocial aspects, treatment approaches, and ethical considerations. Issue 4 (28th August 2018) - França, Katlein; Kumar, Anagha; Castillo, David; Jafferany, Mohammad; Hyczy da Costa Neto, Marcelo; Damevska, Katerina; Wollina, Uwe; Lotti, Torello
Abstract: Trichotillomania (hair pulling disorder) is a fairly common but underreported disorder characterized by recurrent episodes of pulling hair from different parts of the body. Currently classified in Diagnostic and Statistical Manual of Psychiatric Disorders (DSM‐5) under the heading of the "Obsessive–compulsive spectrum and related disorders." The estimated prevalence data suggest that 0.5–2% of the general population suffers from this disorder. Stress and anxiety are directly correlated to the production of trichotillomania symptoms. The psychosocial aspects of trichotillomania are greatly underestimated, but recent literature suggests an increased interest in this neglected area. Although no FDA approved medications are available for the treatment of trichotillomania, a variety of medications including N‐acetylcysteine have shown benefit in case reports. Combined liaison clinics, with an interdisciplinary approach, are highly advisable in the treatment of these cases.